A Criminological Review of Futures Investment Fraud: Digital Platform Exploitation and Social Engineering - Pagala, Maghfirah Ramadhayanti; Abdaud, Faisal; Huzaiman, Huzaiman (SIGn Jurnal Hukum, 2026)
Futures investment fraud has evolved from a conventional economic offense into a systemic financial crisis exploiting the public’s psychological vulnerabilities and absence of digital literacy. This research aims to synthesize the criminological anatomy of these crimes, unveil social engineering tactics within cyber ecosystems, and formulate adaptive legal policy prescriptions to restore victims’ rights. Utilizing a socio-legal research design based on a literature review, the secondary data corpus is analyzed qualitatively by integrating a statute approach and a conceptual approach toward positive law instruments and reputable international journal literature. The research results prove that crime syndicates exploit white-collar anomic pressure through the creation of multi-level recruitment structures, which are subsequently amplified via cultural pseudo-legitimacy and algorithmic manipulation. These exploitation tactics are sustained by information asymmetry and jurisdictional uncertainty within financial supervisory institutions, which subsequently generates a silence cycle among victims due to the impediment of transnational law enforcement by law enforcement agencies. Halting the continuous cycle of these fictitious investment crimes necessitates a sentencing paradigm shift toward the optimization of asset recovery instruments through the application of money laundering criminal offense regulations. These repressive efforts must be synergistically integrated with mutual legal assistance instruments and the enforcement of anti-fraud firewalls at the financial service sector corporate level.